Electronic learning resources and online education technology: issues of effectiveness evaluation - R. Moskalenko, Maxim; M. Dorozhkin, Evgenij; A. Tolstykh, Olga; E. Marakulina, Uliana; V. Mustakimova, Maria (International Journal of Engineering and Technology, 2018)
The relevance of the problem under investigation is due to the widespread use of electronic learning resources and online education technologies in Russian universities and the need to improve their quality for increasing the students learning efficiency. The article aims to study the possibilities for improving the efficiency of e-learning resources and online education technologies and their application specific in teaching students. The leading method of this issue research is the analysis of electronic learning resources and online education technologies use at Russian HEIs. Research results: analysis of electronic learning resources and online education technologies use at Russian HEIs was conducted; approaches for evaluating the efficiency of electronic resources and online education technologies use were developed; recommendations on improving the e-learning resources and online education technologies use were formulated, as well as for developing methodological and pedagogical support for their use in the educational process. The article materials can be useful for: higher-education teaching personnel who one way or another uses e-learning resources and online education technologies in teaching activities; HEIs’ leaders; materials developers and employees of universities that are involved in the practical introduction of e-learning resources and online education technologies into the educational process; students and post-graduate students.